Analysis and Simulation of Tooth Root Fault based on ANSYS / LS- DYNA - Liang Pengwei; Han Zhennan; Ning Shaohui; Wang Dawei (Jixie chuandong)
A pair of undamaged gears and a pair of gears with crack on the root of tooth are simulated and analyzed by using the LS- DYNA,and the change of the acceleration signals and meshing force of any node on the gear can be got. Through the simulation calculation,the meshing force and node acceleration curve can be observed to understand the influence of the meshing impact force on gear body. The study shows that,the influence of the tooth root crack on gear transmission can accurately be simulated by using the LS- DYNA,and all these curves have strict periodicity. A new kind of thought and method for gear fault diagnosis will be provided.